Measurements and Monte-Carlo simulations of the particle self-shielding effect of B4C grains in neutron shielding concrete. (June 2018) - DiJulio, D.D.; Cooper-Jensen, C.P.; Llamas-Jansa, I.; Kazi, S.; Bentley, P.M.
Abstract: A combined measurement and Monte-Carlo simulation study was carried out in order to characterize the particle self-shielding effect of B4 C grains in neutron shielding concrete. Several batches of a specialized neutron shielding concrete, with varying B4 C grain sizes, were exposed to a 2 Å neutron beam at the R2D2 test beamline at the Institute for Energy Technology located in Kjeller, Norway. The direct and scattered neutrons were detected with a neutron detector placed behind the concrete blocks and the results were compared to Geant4 simulations. The particle self-shielding effect was included in the Geant4 simulations by calculating effective neutron cross-sections during the Monte-Carlo simulation process. It is shown that this method well reproduces the measured results. Our results show that shielding calculations for low-energy neutrons using such materials would lead to an underestimate of the shielding required for a certain design scenario if the particle self-shielding effect is not included in the calculations. Abstract : Highlights: Specialized shielding concrete, containing different B4 C grain sizes, was produced. The concrete was exposed to neutrons to study the particle self-shielding effect. A patch for Geant4 was created to include the particle self-shielding effect. Comparison between the simulations and measurements validates the use of this method.